More than Words: Metaphor in Foreign Language Lecturers’ Talk - markus deli girik allo (UKI TORAJA, 2016)
The research aims to investigate the metaphor used in Foreign Language Lecturers’ Talk.The subjects of this research were Lecturers at English Education Study Program of FKIPUKI Toraja. The results of the research revealed that the metaphor used in Foreign LanguageLecturers’ Talk are: a)That's where the name of the price of ink, b) going to the bamboo trees everySunday, c) Why are you looking for disease?”, d) “I asked to delete it, replaced the previous study, ifyou're exactly similar with it means you have cheated, beautiful playing, you have to play beautifully,e) Then creating a definition not like this model, set good example, there are several definitions ofwriting they are, then if your model like that, this is a direct fire!, f)